Bilaterally Asymmetric Helical Myofibrils in Ascidian Tadpole Larvae - Matsuo, Koichi; Tamura, Ryota; Hotta, Kohji; Okada, Mayu; Takeuchi, Akihisa; Wu, Yanlin; Hashimoto, Koh; Takano, Hidekazu; Momose, Atsushi; Nishino, Atsuo (Frontiers in Cell and Developmental Biology, 2021)
The locomotor system is highly bilateral at the macroscopic level. Homochirality of biological molecules is fully compatible with the bilateral body. However, whether and how single-handed cells contribute to the bilateral locomotor system is obscure. Here, exploiting the small number of cells in the swimming tadpole larva of the ascidian Ciona, we analyzed morphology of the tail at cellular and subcellular scales. Quantitative phase-contrast X-ray tomographic microscopy revealed a high-density midline structure ventral to the notochord in the tail. Muscle cell nuclei on each side of the notochord were roughly bilaterally aligned. However, fluorescence microscopy detected left-right asymmetry of myofibril inclination relative to the longitudinal axis of the tail. Zernike phase-contrast X-ray nanotomography revealed the presence of left-handed helices of myofibrils in muscle cells on both sides. Therefore, the locomotor system of ascidian larvae harbors symmetry-breaking left-handed helical cells, while maintaining bilaterally symmetrical cell alignment. These results suggest that bilateral animals can override cellular homochirality to generate the bilateral locomotor systems at the supracellular scale.